How the vegetarian diet influences recreational and professional athletes’ physical performance: A systematic review - Araújo, Marina Nascimento de (2021)
Vegetarianism has been getting increasing attention over the years, in society in general and in sport in particular. However, the growth in the number of people following a meatless diet notwithstanding, vegetarianism should be practiced with caution, especially by professional and recreational athletes, considering the possible lack of certain nutrients and decline in their physical performance. Therefore, the present review aimed to determine whether following a vegetarian diet influences recreational and professional athletes’ physical and sports performance. A search of the databases Medline/Pubmed, Scopus, Web of Science, and Lilacs gave 343 relevant articles; however, only 15 of these focused on the vegetarian diet and physical performance, in accordance with the inclusion criteria. These studies compared the vegetarian diet with the omnivorous diet, and found that it did not negatively influence physical performance. Moreover, those who followed a vegetarian diet seemed to have a higher volume of maximum oxygen (V̇O2 max), which positively influenced their performance. In conclusion, following a plant-based diet does not seem to harm recreational and professional athletes.